The Role of Attachment Trauma and Disintegrative Pathogenic Processes in the Traumatic-Dissociative Dimension - Farina, Benedetto; Liotti, Marianna; Imperatori, Claudio (Frontiers in Psychology, 2019)
Epidemiological, clinical and neurobiological studies of the last 30 years suggest that traumatic attachments during the early years of life (developmental trauma) cause a specific vulnerability to psychopathological developments based on dissociative pathogenic processes that interferes … Dissociative processes are manifested in various symptoms: arousal dysregulation, dissociative detachment (dissociation of consciousness: e.g. depersonalization), dissociative compartmentalization (dissociation among ego states), somatoform symptoms (somatoform dissociation), emotional and behavioral regulation difficulties and severe interpersonal problems. In adult clinical populations dissociative processes and the related symptoms may either contribute to the genesis of well-defined disorders such as dissociative, borderline and complex post-traumatic, or variably occur in many other DSM or ICD diagnostic categories complicating their clinical pictures and worsening the prognosis. The clinical complexity of developmental trauma requires specific training to enable mental health professionals to recognize the signs of traumatic developments and to implement specific treatment strategies. Besides an introductory overview of the literature on clinical problems and treatment strategies for the sequels in adulthood of developmental trauma, this paper offers an outline on three issues on the adult outcome of developmental trauma and its therapy: the role of disorganized attachment, the need to distinguish disintegrative and dissociative pathogenic processes and the usefulness of traumatic-dissociative psychopathological dimension for clinical reasoning of the contributions of attachment theory and research to the developmental psychopathology of adult disorders related to cumulative traumas in childhood.